SEJARAH DAN DINAMIKA PIMPINAN CABANG MUHAMMADIYAH KEBAYORAN BARU - Muhammad Maududi, Mukhlish; Supendi, Mohammad (Universitas Muhammadiyah Prof DR HAMKA, 2020)
Muhammadiyah Kebayoran Baru Branch is one of the oldest branches in Jakarta, with a well-developed Charity Business, such as Leading Schools and Hospitals and the success of organizing da'wah, is also the place for the establishment of the Muhammdiyah Vigilance and Preparedness Command